2004
DOI: 10.1158/0008-5472.can-04-3620
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Regulatory Subunit Type 1A of Protein Kinase A Leads to Endocrine and Other Tumors

Abstract: Mutations of the human type I␣ regulatory subunit (RI␣) of cyclic AMP-dependent protein kinase (PKA; PRKAR1A) lead to altered kinase activity, primary pigmented nodular adrenocortical disease, and tumors of the thyroid and other tissues. To bypass the early embryonic lethality of Prkar1a ؊/؊ mice, we established transgenic mice carrying an antisense transgene for Prkar1a exon 2 (X2AS) under the control of a tetracyclineresponsive promoter. Down-regulation of Prkar1a by up to 70% was achieved in transgenic mous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 18 publications
4
74
0
Order By: Relevance
“…Down-regulation of Prkar1a was shown in vitro and in vivo at both mRNA and protein levels (28), and the mice were observed to develop thyroid hyperplasia similar to that observed in human patients (29). These mice were also prone to the development of lymphomas and sarcomas, although these tumors are not frequent in Carney complex patients, and their significance is unknown.…”
Section: Discussionmentioning
confidence: 84%
“…Down-regulation of Prkar1a was shown in vitro and in vivo at both mRNA and protein levels (28), and the mice were observed to develop thyroid hyperplasia similar to that observed in human patients (29). These mice were also prone to the development of lymphomas and sarcomas, although these tumors are not frequent in Carney complex patients, and their significance is unknown.…”
Section: Discussionmentioning
confidence: 84%
“…Although PKARI␣ may act as a "tumor suppressor" in CNC, previous studies have also reported that PKARI␣ facilitates the cell proliferative signaling of hormones and growth factors in certain types of cancer cells (46) and depletion of PKARI␣ effectively inhibits transcription of certain genes and growth of tumor cells (47). Thus, PKARI␣ may augment or inhibit cellular proliferation in a cell type-specific manner.…”
Section: Pp2a Exists In a Complex With Rsk1⅐pka⅐d-akap1 And Ht31mentioning
confidence: 99%
“…Perhaps, the best example of a RET fusion partner, whose altered function may contribute to neoplastic transformation is the regulatory subunit type I-a of protein kinase A (PRKAR1A) that is involved in RET/ PTC2. PRKAR1A is, indeed, a bona fide tumor suppressor (65) and its ablation in the mouse induced the formation of thyroid tumors (66). The knowledge about the function of the other RET fusion partners is limited.…”
Section: Molecular Mechanisms Of Activation Of Ret/ptc Oncoproteinsmentioning
confidence: 99%